2018
DOI: 10.1038/s41598-018-25470-0
|View full text |Cite
|
Sign up to set email alerts
|

Topologically knotted deubiquitinases exhibit unprecedented mechanostability to withstand the proteolysis by an AAA+ protease

Abstract: More than one thousand knotted protein structures have been identified so far, but the functional roles of these knots remain elusive. It has been postulated that backbone entanglement may provide additional mechanostability. Here, we employed a bacterial proteasome, ClpXP, to mechanically unfold 52-knotted human ubiquitin C-terminal hydrolase (UCH) paralogs from their C-termini, followed by processive translocation into the proteolytic chamber for degradation. Our results revealed unprecedentedly slow kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 52 publications
(56 reference statements)
1
48
0
Order By: Relevance
“…We took advantage of the widely adopted ClpP protease degradation assay using GFP-ssrA as the model substrate. Loss of GFP fluorescence is used as a reporter to monitor substrate degradation by ClpAP as a function of time (26,27). The results showed that over time, wild-type ClpP effectively degraded GFP-ssrA with a half-life of about 30 min (Fig.…”
Section: The Clpp Protein But Not Its Protease Activity Plays a Critimentioning
confidence: 96%
See 1 more Smart Citation
“…We took advantage of the widely adopted ClpP protease degradation assay using GFP-ssrA as the model substrate. Loss of GFP fluorescence is used as a reporter to monitor substrate degradation by ClpAP as a function of time (26,27). The results showed that over time, wild-type ClpP effectively degraded GFP-ssrA with a half-life of about 30 min (Fig.…”
Section: The Clpp Protein But Not Its Protease Activity Plays a Critimentioning
confidence: 96%
“…GFP fluorescence based-degradation assays were carried out in PD buffer (25 mM HEPES, pH 7.5, 100 mM KCl, 25 mM MgCl2, 1 mM DTT, 10% glycerol) containing 3 µM GFP-ssrA as substrate and ATP regeneration system (16 mM creatine phosphatase, 0.32 mg/mL creatine kinase) as described previously (27). In brief, 0.1 μM ClpX6 and 0.3 μM ClpP14 or its variants were mixed at 30 °C and let stand for 2 min.…”
Section: Protein Degradation Assaymentioning
confidence: 99%
“…There is a plethora of studies in the literature, both experimental and computational, which analyzed specific model systems and proposed several biological functions. It has been proposed that knotted proteins have enhanced thermal (20,26), mechanical (26,27,128) and structural (127) stabilities. Another possibility is that knots help shape and stabilize the active site of enzyme (129)(130)(131), and in some cases it has even been suggested that knots can control enzymatic (130) and signaling activity (132).…”
Section: Functional Advantages Of Knots In Proteinsmentioning
confidence: 99%
“…The realization that knotted proteins exist motivated the search for the functional advantages that knots may convey to their carriers. The analysis of specific model systems has put forward the idea that knots could enhance thermal (20,26) or mechanical stability (27), just to mention a few examples. However, a universal role for knots in proteins has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our substrate was able to be degraded even in the absence of the Rpn10 UIM domain, while in previous work from the Martin lab, degradation of an Rsp5-ubiquitinated GFP-containing substrate was completely dependent on Rpn10 37 . Possibly this substrate cannot bind to Rpn13 in a productively positioned manner or has different unfolding requirements than our substrate, as the topology and stability of a substrate may affect the force needed to unfold it 16,61,62 . Alternatively, reconstituted proteasome could be missing physiological modifications or proteasome-associated proteins (such as shuttle factors) that allow Rpn13 to be used productively or increase the proteasome's unfolding ability.…”
Section: Figurementioning
confidence: 99%